If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + (3x + 6) = 5 Reorder the terms: 3x + (6 + 3x) = 5 Remove parenthesis around (6 + 3x) 3x + 6 + 3x = 5 Reorder the terms: 6 + 3x + 3x = 5 Combine like terms: 3x + 3x = 6x 6 + 6x = 5 Solving 6 + 6x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6x = 5 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = 5 + -6 6x = 5 + -6 Combine like terms: 5 + -6 = -1 6x = -1 Divide each side by '6'. x = -0.1666666667 Simplifying x = -0.1666666667
| 3(4)+5y=17 | | 15t-5t^2+3t^32=0 | | 3n^2-6n+7=0 | | 3(x+4)+2x-6+5(-x-1)= | | Y=1(x-5)+3 | | 14=2L+4W | | (3a^2)-6x-9= | | 3a+6+5a-2a=2 | | 4(w-2.1)=.6 | | 9x^8-4x^7-5x-18=0 | | 4y=165 | | 3(x-2)+7=4(2+x) | | 9+m=15 | | 3x+6=8x-12 | | -3(2x-5)=-3 | | (n+5)-16=1 | | x^2+14x+27-42=(x-1)(x+15) | | 20x+7-6+3x=21 | | 4.2= | | -x+-7x=-40+-9 | | x+x+3=3y+y+1 | | -108pie=6piej | | -40(x-1)(2x)(x-4)=0 | | 7(b+3)-2b= | | 6X=14+2 | | -97-24-130= | | 0.555555556x=10 | | 4x-2(2x+1)=6 | | -x+6x-10=40 | | 6(x-3)+10=2(3x-5) | | -8/3x-5/2=-3/2 | | -3x^2-31x+23=0 |